A Strategic Approach Toinformation Technology Management - Dr Anil Kumar Mahra (International Journal of Advanced Science and Technology, 2019)
Strategic information technology management encompassesresolution-making about business objectivestogether with deployment of plans and proceduresconcerning the distribution of technological resources.As such, strategic information technology management is anactive and complex procedurewhichencompassesattention of internal and external factors of organization. This paper discussed the strategicapproach to information technology management. In the context of information technology it may bemaintained that such methodssignifylimited approaches to strategic management that disregard thecomposite, implanted and vibrant nature of newbusiness organizations. Therefore, the causes whystrategic plans fail are taken to deliverand discuss for the evaluation of the potential contribution of arange of systems methodologies to the strategic management process.This paper systematicallydiscussesstrategic information technology management that shows value not only in using the approaches inseparation but also in using them in a corresponding and flexible way